2020
DOI: 10.1021/acs.nanolett.0c03453
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Manipulation of Bilayer Graphene Quantum Dots with Broken Rotational Symmetry and Nontrivial Topology

Abstract: Electrostatically defined quantum dots (QDs) in Bernal stacked bilayer graphene (BLG) are a promising quantum information platform because of their long spin decoherence times, high sample quality, and tunability. Importantly, the shape of QD states determine the electron energy spectrum, the interactions between electrons, and the coupling of electrons to their environment, all of which are relevant for quantum information processing. Despite its importance, the shape of BLG QD states remains experimentally u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Researchers have detected the valley and Zeeman splittings with a spin g-factor g s ≈ 2 in single electron charging of gate-defined bilayer GQDs [156], and the valley splitting linearly depends on the external perpendicular magnetic field [156,157]. Ge et al [159] have directly visualized the wave function shape of bilayer GQD states with a robust broken rotational symmetry, which is contributed to the low energy anisotropic bands. And they also demonstrated that the nontrivial band topology of bilayer graphene could be manifested and manipulated by imaging quantum interference patterns in bilayer GQDs.…”
Section: Novel Bound States In Bilayer Gqdsmentioning
confidence: 99%
“…Researchers have detected the valley and Zeeman splittings with a spin g-factor g s ≈ 2 in single electron charging of gate-defined bilayer GQDs [156], and the valley splitting linearly depends on the external perpendicular magnetic field [156,157]. Ge et al [159] have directly visualized the wave function shape of bilayer GQD states with a robust broken rotational symmetry, which is contributed to the low energy anisotropic bands. And they also demonstrated that the nontrivial band topology of bilayer graphene could be manifested and manipulated by imaging quantum interference patterns in bilayer GQDs.…”
Section: Novel Bound States In Bilayer Gqdsmentioning
confidence: 99%
“…In bilayer graphene, recent experiments achieve confinement of charge carriers in one-and zero-dimensional structures by electrostatic gating [4][5][6][7][8][9][10] . To electrostatically define a nanostructure in bilayer graphene multiple gates locally modulate the bilayer graphene band gap and charge carrier density, cf.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of two or more coupled quantum dots in BLG have also been studied experimentally and theoretically [25][26][27]. Recently, the electronic density within BLG quantum dots has been visualized using the tip of a scanning tunneling microscope (STM) [28,29]. The valley properties of an electrostatically confined BLG quantum dot have been investigated experimentally [30,31], and a valley filter device based on these properties has been proposed [32].…”
Section: Introductionmentioning
confidence: 99%